Long-term efficacy and toxicity of concurrent chemoradiotherapy with nedaplatin and S-1 for head and neck squamous cell carcinoma. Issue 6 (December 2019) - Okuda, Hiroshi; Ohnishi, Masami; Takahashi, Hiroki; Takagi, Chiaki; Takada, Natsuki; Ohashi, Toshimitsu
Abstract: Objective: The present study aimed to retrospectively analyze the long-term efficacy and toxicity of concurrent chemoradiotherapy with nedaplatin and S-1 for head and neck squamous cell carcinoma. Methods: The study enrolled 53 patients (23 with stage II disease, 13 with stage III disease, and 17 with stage IV disease). S-1 was administered orally twice a day for 14 days, followed by a two-week rest period. Nedaplatin was intravenously administered on day 4. Where possible, two courses of chemotherapy were performed. Radiotherapy was started with the administration of S-1. We analyzed the clinical response, survival rate, acute adverse events, and late swallowing toxicity. Results: The complete response rates for the primary tumor and neck lymph node metastases were 94.3% and 79.3%, respectively. The five-year overall survival rate was 79.5%, the five-year disease-specific survival rate was 84.8%, and the five-year relapse-free survival rate was 73.7%. The main acute adverse events were leukopenia, neutropenia, mucositis, and dermatitis. No patient had severe nephrotoxicity. Late swallowing toxicity was observed in 13 patients. Conclusions: The low toxicity, and low nephrotoxicity of chemoradiotherapy with nedaplatin and S-1 have a positive impact on long-term survival. The combination of nedaplatin and S-1 can be used instead of cisplatin and 5-ﬂuorouracil as a safer regimen, especially in patients with some complications and those requiring treatment in an outpatient setting.